STRATEGI INOVASI PROSES DAN PRODUK TERHADAP KINERJA MANAJERIAL YANG DIMEDIASI SISTEM KONTROL - Rosyati, Rosyati (Universitas Muhammadiyah Magelang, 2008)
The objective of this study is testing of effect between process innovation strategy, product innovation strategy to managerial performance and testing of effect between process innovation with operational control system to managerial performance, and testing of effect between product innovation with operational control to managerial performance. The methods of sampling data which is used in this study is convenience sampling. The statisticanalysis media which is used is regression analysis. The research sample included manager, head section and head subsection of printing companies in Magelang district which induced 31 persons. The result of the study shows that there was an effect fro process innovation strategy managerial performance. There was an effect between product innovation with operational control system system to managerial performance. And there was a positif effect from the product innovation interaction with operational control system to managerial performance. Related to the result, controlling the budget was suggested or predicted as early as possible in order to increasing the affectivity of the company budget especially in planning and controlling activity.